2018
DOI: 10.3390/app8030456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Stage Temperature and Rotation Rate on the Magneto-Optical Quality of RF-Sputtered Bi2.1Dy0.9Fe3.9Ga1.1O12 Garnet Thin Films

Abstract: Abstract:Highly bismuth-substituted iron garnet thin films are prepared on quartz substrates by using a radio frequency (RF) magnetron sputtering technique. We study the factors (process parameters associated with the RF magnetron sputter deposition technique) affecting the magneto-optical (MO) properties of ferrite garnet films of composition Bi 2.1 Dy 0.9 Fe 3.9 Ga 1.1 O 12 . All films show high MO response across the visible range of wavelengths after being annealed. In particular, the effects of substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…synthesizing the garnet-oxides composites, applying post-deposition oxygen plasma treatment, and garnet layers deposited using different substrate stage rotation rates (rpm). , improved optical and MO properties observed in oxygen plasma treated garnet films, and the garnet layers deposited using various substrate stage rotation rates (rpm) [13,37,33,38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…synthesizing the garnet-oxides composites, applying post-deposition oxygen plasma treatment, and garnet layers deposited using different substrate stage rotation rates (rpm). , improved optical and MO properties observed in oxygen plasma treated garnet films, and the garnet layers deposited using various substrate stage rotation rates (rpm) [13,37,33,38].…”
Section: Resultsmentioning
confidence: 99%
“…The variations in RF sputtering process parameters (substrate stage temperature and rotation rate) influence the properties (films' stoichiometry and MO quality through variations in both the specific Faraday rotation and the optical absorption coefficients) of garnet films. From this study we concluded that the MO characteristics can be tuned and optimized for use in various magnetic field-driven nano-photonics and integrated optics devices with an addition of a flexible and cost-effective approach for the design and development of new, high-quality, and application-specific MO materials for various photonics and integrated-optics applications [38].…”
Section: Investigation Of Deposition Process Parameter Effects On Gar...mentioning
confidence: 94%
See 1 more Smart Citation
“…The variations in RF sputtering process parameters (substrate stage temperature and rotation rate) influence the properties (films' stoichiometry and MO quality through variations in both the specific Faraday rotation and the optical absorption coefficients) of garnet films. We concluded from this study that the MO characteristics can be tuned and optimized for use in various magnetic field-driven nano-photonics and integrated optics devices with the addition of a flexible and economical approach for the design and development of new, high-quality, and application-specific MO materials for various photonics and integrated-optics applications [38].…”
Section: Investigation Of Deposition Process Parameter Effects On Gar...mentioning
confidence: 96%
“…Modified ferrite garnets, especially Bi-substituted iron garnets (with compositions close to Bi 3 Fe 5 O 12 ) have very high specific Faraday rotations across the visible light spectrum and relatively low optical absorption in the near-infrared spectral region. Multiple process parameters relevant to the synthesis of substituted iron garnet materials have a significant influence on their physical (structural, optical and magnetic) properties [30,31,32,33]. However, it is always challenging to develop application-specific substituted ferrite garnet thin-film materials with high quality (in terms of their structural, optical and magneto-optical properties being optimized simultaneously) by using physical vapor deposition techniques.…”
Section: Introductionmentioning
confidence: 99%